2021
DOI: 10.1002/ptr.7138
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic activities of phytosteroids in inflammatory diseases: Mechanism of action and therapeutic potentials

Abstract: Natural products and their derivatives are known to be useful for treating numerous diseases since ancient times. Because of their high therapeutic potentials, the use of different medicinal plants is possible to treat varied inflammation‐mediated chronic diseases. Among natural products, phytosteroids have emerged as promising compounds mostly because they have diverse pharmacological activities. Currently, available medications exert numerous systemic toxicities, including hypertension, immune suppression, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 145 publications
(190 reference statements)
0
22
0
Order By: Relevance
“… 51 , 52 Sitosterol is one of the bioactive phytosterols, which has shown the potential anti-inflammatory activity and antihistamine activity by inhibiting the release of histamine from the MCs, expression of TNF-α, and blocking the activity of cyclooxygenase-2, inducible nitric oxide synthase, and extracellular-signal regulating kinase pathways. 53 Moreover, it is proved that sitosterol treatment could significantly increase the tidal volume and decrease the respiration rate of asthmatic guinea pigs and protect against airway inflammation in lung tissue histopathology. 54 All in all, these studies about pivotal ingredients of WMW lend support to our findings of HUB gene GO and KEGG pathway enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 51 , 52 Sitosterol is one of the bioactive phytosterols, which has shown the potential anti-inflammatory activity and antihistamine activity by inhibiting the release of histamine from the MCs, expression of TNF-α, and blocking the activity of cyclooxygenase-2, inducible nitric oxide synthase, and extracellular-signal regulating kinase pathways. 53 Moreover, it is proved that sitosterol treatment could significantly increase the tidal volume and decrease the respiration rate of asthmatic guinea pigs and protect against airway inflammation in lung tissue histopathology. 54 All in all, these studies about pivotal ingredients of WMW lend support to our findings of HUB gene GO and KEGG pathway enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We further showed that ADRB2 bound most tightly to cyclopamine; CHRM1 to beta-sitosterol; NR3C1 to mairin; OPRD1 to tabernemontanine, moupinamide, epiquinidine; and OPRD1 to tabernemontanine, moupinamide, epiquinidine, 3-Hydroxymethylenetanshinquinone, and (-)-Tabernemontanine. Beta-sitosterol has anti-inflammatory, anti-tumor, antioxidant, anti-hyperlipidemic, and antihypertensive effects ( 82 84 ), and moupinamide is also anti-inflammatory ( 85 ). Inflammatory processes are involved in the development of hypertension ( 86 , 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dioscin inhibits the M2 polarization of macrophages in the JNK and STAT3 pathways, thereby triggering antitumor immunity [ 36 ]. Other studies have further shown that dioscin has similar pharmacokinetic characteristics to dexamethasone [ 37 ] and exerts antiarthritis effects by inhibiting the immune response of Th17 cells [ 38 ]. In addition, dioscin inhibits osteoclast differentiation and bone resorption by downregulating the Akt signaling cascade [ 39 ].…”
Section: Discussionmentioning
confidence: 99%